The Role of Open and Distance Learning (ODL) in Promoting Access to Women's Education in Northwestern Nigeria: A Case Study of the National Open University of Nigeria (NOUN) - Shehu Usman Adamu; Bala Kwata Waziri; Adewale Adesina; Babangida Iro (West African Journal of Open and Flexible Learning)
A survey was conducted using the National Open University database to ascertain the number of women from the northwestern states of Jigawa, Kaduna, Kano, Katsina, Kebbi, Sokoto and Zamfara studying in the University based on the admission records from 2018 to 2022. The study also checked the faculties where those women registered during the last 4 years to determine the role of Open and Distance Learning in giving women access to higher education. A total of twenty-five thousand three hundred and sixteen women enrolled in the National Open University of Nigeria in the period under review with Kaduna Study Centre having the highest figure of 8,791, followed by Kano with 4,995 with Katsina, Dutse, Sokoto, Gusau and Birnin Kebbi having 2,554., 1,607., 1,129., 1,000 and 971 respectively while other smaller centres in Northwest had 4,263. Concerning programmes of study in various faculties, the Faculty of Health Sciences had the highest enrollment figures of ten thousand four hundred and twenty-four (10,424) representing 41.1% followed by the Faculty of Science with three thousand eight hundred and thirty-eight (3,838) representing 15.1%. Faculties of Agric, Arts, Education Law and Management had enrolment figures of 134 (0.52%), 634 (2.53%), 3,921 (15.4%8), 98 (0.38%), 2,954 (11.66%) respectively while Faculty of Social Sciences had 3,311 (13.07%). Generally, Open and Distance Learning has given women tremendous opportunities to higher education in the region considering that over twenty-five thousand women registered for various programmes using the ODL during the period under review.